Democratic Republic of the Congo : Poverty Reduction and Growth Facility-Request for an Extension. (IMF Staff Country Reports; Country Report ;, 2005)
This paper discusses Congo's Request for an Extension for the Poverty Reduction and Growth Facility (PRGF). The extension will provide additional time for the completion of the fifth review under the PRGF. The review was delayed owing to slippages in the second half of 2004 that had led to a depreciation of the Congo franc and high inflation. As a result, three quantitative performance criteria for end-September 2004 were not met. The IMF staff supports the authorities' request for an extension of the arrangement through October 31, 2005.